PENGARUH PROFITABILITAS, LIKUIDITAS DAN LEVERAGE TERHADAP HARGA SAHAM USAHA MAKANAN DAN MINUMAN DI JII - Ratna Sariputri; Deny Yudiantoro (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
This study was conducted to see the effect of profitability, liquidity and leverage on the stock price of the food and beverage business in the Jakarta Islamic Index (JII) in 2016-2020. The population of this study were 7 companies listed in the Food and Beverage Business Stock in the Jakarta Islamic Index 2016-2020 which consisted of PT. Unilever Indonesia, PT. Kalbe Farma, PT. Indofood CBP Sukses Makmur Tbk, Indofood Sukses Makmur, PT Siantar Top Tbk, PT Wilmar Cahaya Indonesia Tbk, and PT. Indonesian Mayor. The data were analyzed using the purposive sampling method, while the sample in this study was 35 samples of financial statement data in the 2016-2020 period at food and beverage companies that were members of JII. Data were analyzed by panel data regression and f-test used to determine the reliability of the study with a significance level of 5%. The results show that profitability, leverage and liquidity simultaneously affect stock prices. Partially, profitability, liquidity and leverage have a positive and significant effect on stock prices